2010
DOI: 10.2169/internalmedicine.49.3409
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Refractory Enteropathy-Associated T-Cell Lymphoma Using High-Dose Chemotherapy and Autologous Stem Cell Transplantation

Abstract: A 65-year-old woman presented with a 6-month history of abdominal pain and watery diarrhea. Type II enteropathy-associated T-cell lymphoma (EATL) was diagnosed based on the clinical presentation and pathological examination of the tumor. The patient received combination chemotherapy but did not achieve remission. Subsequently, high-dose therapy (HDT) and autologous stem cell transplantation (ASCT) were performed. After these therapies, she achieved complete remission, which has been sustained for 18 months. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Surgery, chemotherapy and radiotherapy are all used to treat MEITL, although these treatments have shown poor overall outcomes[ 21 ]. Although several studies have demonstrated the benefit of autologous stem cell transplantation[ 22 - 25 ], there is no standardized treatment strategy. Moreover, MEITL often requires emergency surgery due to intestinal perforation or obstruction, and the lesion has usually spread before it is diagnosed[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, chemotherapy and radiotherapy are all used to treat MEITL, although these treatments have shown poor overall outcomes[ 21 ]. Although several studies have demonstrated the benefit of autologous stem cell transplantation[ 22 - 25 ], there is no standardized treatment strategy. Moreover, MEITL often requires emergency surgery due to intestinal perforation or obstruction, and the lesion has usually spread before it is diagnosed[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a considerable improvement in survival after SCT has been seen; however, younger patients with few comorbidities who can tolerate the high-dose chemotherapy will probably benefit more than any other population. This therapeutic option needs to be considered cautiously, as many of them present with poor performance status and malnutrition, which may worsen tolerance to chemotherapy or impair them to finalise treatment [ 1 , 6 , 40 ].…”
Section: Discussion/literature Reviewmentioning
confidence: 99%